Quantifying hyperoxia-mediated damage to mammalian respiratory cilia-driven fluid flow using particle tracking velocimetry optical coherence tomography - Gamm, Ute A. (J Biomed Opt, 2015)
Oxygen supplementation [hyperoxia, increased fraction of inspired oxygen ([Formula: see text])] is an indispensable treatment in the intensive care unit for patients in respiratory failure. Like other treatments or drugs, hyperoxia has a risk-benefit profile that guides its clinical use. While hyperoxia is known to damage respiratory epithelium, it is unknown if damage can result in impaired capacity to generate cilia-driven fluid flow. Here, we demonstrate that quantifying cilia-driven fluid flow velocities in the [Formula: see text] regime (sub-0.25 in./min regime) reveals hyperoxia-mediated damage to the capacity of ciliated respiratory mucosa to generate directional flow. Flow quantification was performed using particle tracking velocimetry optical coherence tomography (PTV-OCT) in ex vivo mouse trachea. The ability of PTV-OCT to detect biomedically relevant flow perturbations in the [Formula: see text] regime was validated by quantifying temperature- and drug-mediated modulation of flow performance in ex vivo mouse trachea. Overall, PTV-OCT imaging of cilia-driven fluid flow in ex vivo mouse trachea is a powerful and straightforward approach for studying factors that modulate and damage mammalian respiratory ciliary physiology.